KARAKTERISTIK SYMMETRIC NUCLEAR MATTER PADA TEMPERATUR NOL - Annisa Fitri; Anto Sulaksono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Investigation of characteristics of Symmetric Nuclear Matter is done to check the instability of nuclear structure when heavy ion collisions, which are influenced by non linear terms of the extended relativistic mean field equations. The calculation of the variable compressibility, pressure, the effective mass of nucleons, and sound velocity is done numerically using finite derivatives. The use of nonlinear parameters affect the relationship between the ratio of the density with thermodynamic variables obtained. Non linear terms of meson field interaction give effect to the characteristics of nuclear matter. Representation between the ratio of the density and sound velocity comparison with the speed of light is relevant, and does not indicate unphysical behavior. Keywords: compressibility, mass, meson, nucleons, pressure, sound, velocity.